Intervenções topológicas na rede de distribuição para minimização do risco de não detecção de ilhamento - Ribeiro, Nádia Carolina (2024)
The increasing integration of distributed generation into the electrical system results, as a key benefit, in the diversification of the energy matrix through various sources, mainly renewable ones. However, the integration of distributed generators also presents challenges, among which is the detection of islanding. Islanding occurs when a portion of the distribution network operates while being electrically isolated from the utility grid due to the presence of distributed generators. This condition triggers a series of implications, especially regarding safety, making it necessary to disconnect the generators through the activation of protection schemes. Various protection techniques have been developed with the purpose of detecting islanding, with passive techniques being the most widely used. However, these techniques have a non-detection zone that prevents action under conditions of low active and reactive power imbalances. Given this context, the objective of this master’s dissertation is to evaluate how topological interventions in power distribution networks can influence the risk of failure in islanding detection through variations in active and reactive power imbalance. The study employs an anti-islanding protection system composed of voltage and frequency protection functions and uses OpenDSS and ATP software jointly to obtain the results. Subsequently, the impacts of the power and connection location of capacitor banks, the connection location of automatic reclosers, and network reconfiguration maneuvers on islanding detection are evaluated. Several simulations were carried out for the analysis of each scenario, and the results indicate that all three options are viable approaches to addressing this issue without compromising the primary function of these devices and tools.